Análise da disposição e tratamento dos efluentes de abatedouros - Aquino, Raul Santos de (Universidade Federal Rural do Semi-Árido, 2018)
Faced with the population growth observed in recent years is the unbridled increase in consumption, including in the slaughtering sector. All this intake creates a great concern of the governmental organs, since the increase of this ends up generating a greater amount of waste that, in turn, can come to pollute soils and rivers. The applications of environmental management rules have significantly reduced the generation of waste in the food industry. But despite these advances, generation and disposal are high and are not usually adequate to current legislation, effluent treatment is an option to avoid environmental damage. In this way, this work aimed to study the treatment adopted and the disposal of the effluents generated in five (5) slaughterhouses located in the Pau dos Ferros microregion. Initially, a field survey was carried out and it was identified that these generated effluents are collected by a private company and treated at a Sewage Treatment Plant - ETE of the same. The parameters considered for the analysis were physical, chemical and biological (BOD, COD, pH, ammoniacal nitrogen, total and sedimentable solids, total coliforms and thermotolerant) of the years 2014,2016 and 2018. The values obtained were compared with resolution CONAMA nº 430/2011, 357/2005 and CETESBE and calculated the removal efficiency after the treatment performed. The results show that the treatment used is effective in the removal of BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), Ammoniacal Nitrogen and Total and Thermotolerant Coliforms. On the other hand, it presents low efficacy in the removal of total and sedimentary solids.
Keywords: Esgoto industrial; Remoção biológica; Parâmetros; Despejo; Matéria orgânica; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA